Biomedical Applications of DNA‐Based Molecular Devices. Issue 10 (2nd April 2019) - Liu, Shaoli; Jiang, Qiao; Wang, Yuanning; Ding, Baoquan
Abstract: Strict Watson–Crick base pairing and availability by automated synthesis have allowed deoxyribonucleic acid (DNA) molecules to be used as engineerable building blocks for constructing versatile nanostructures. In recent decades, with the development of DNA nanotechnology, a range of DNA‐based dynamic molecular devices with sophisticated nanostructures have been designed and constructed. Featuring programmability and biocompatibility, the applications of DNA‐based nanodevices have been extensively focused on the interfaces of biological systems. This review summarizes the recent progress in the design of DNA devices exhibiting programmable functions for biomedical applications. In vitro and in vivo applications of DNA‐based nanodevices in cellular imaging and systemic drug delivery are highlighted. The challenges and open opportunities are also discussed. Abstract : DNA‐based robotic devices have been designed and constructed in recent decades. Featuring programmability and biocompatibility, the applications of DNA devices have been extensively focused on the interfaces of biomedical systems. In this review, the recent developments of DNA devices working in cellular environments and animal levels are summarized.